Chemical Characteristics and Microbial Identification of Fish Fermented Food by Flores Ethnic - Nur R. Adawiyah Mahmud; Ernawati Hasan; Basyiran Daud; Kumala Sari; Ernawati; Cahyaningtyas (Nusantara Science and Technology Proceedings, 2023)
Mudu and Mbarase are two local fish-fermented foods that have been known for a long time in the culture of the Flores community. These two fermented foods were made using a high-salt fermentation process. Mudu is made from fish (tuna and Rastrelliger family) innards while Mbarase is made from rabbitfish (Siganus Sp.). This study aimed to analyze the chemical characteristics and identify microbial content in these two samples. The chemical characteristic here was proximate analysis and the microbial identification was done for lactic acid bacteria (LAB) identification. Proximate analysis of samples was done using the AOAC standard method. LAB identification was done by morphology observation with a clear zone around the colony, gram test, and catalase test. For the proximate analysis, Mudu contains 21.022% carbohydrate, 11.8% protein, 0.42% fat, 6.587% ash, 60.171% water, and 1.94% fiber. Mbarase contains 7.732% carbohydrates, 25.19% protein, 4.558% fat, 5.13% ash, 57.29% water, and 0.16% fiber. A clear zone can be seen in the Mbarase sample and slightly seen in the Mudu sample. Lactic acid bacteria isolated from Mbarase have antibacterial activity to E. coli and A. hydrophilla. Mbarase and Mudu may become a good source of nutrients as they have high protein, low fat, and ash. These fish fermented food also have probiotic potentials as it has antibacterial activity against pathogen bacteria.